Azad hinda phauja aur neta ji - Soni, Vedprakaś (Dilli : Janavani Prakaśan, 2010)
On Subhas Chandra Bose, 1897-1945, Indian freedom fighter and leader of Indian National Army.
Keywords: indijska povijest -- borba za nezavisnost -- indijski nacionalizam; Subhaš Candra Bose - biografija -- Indian National Army